Limonin: A Review of Its Pharmacology, Toxicity, and Pharmacokinetics - Shunming Fan (Molecules, 2019)
Limonin is a natural tetracyclic triterpenoid compound, which widely exists in Euodia rutaecarpa (Juss.) Benth., Phellodendron chinense Schneid., and Coptis chinensis Franch. Its extensive pharmacological effects have attracted considerable attention in recent years. However, there is no systematic review focusing on the pharmacology, toxicity, and pharmacokinetics of limonin. Therefore, this review aimed to provide the latest information on the pharmacology, toxicity, and pharmacokinetics of limonin, exploring the therapeutic potential of this compound and looking for ways to improve efficacy and bioavailability. Limonin has a wide spectrum of pharmacological effects, including anti-cancer, anti-inflammatory and analgesic, anti-bacterial and anti-virus, anti-oxidation, liver protection properties. However, limonin has also been shown to lead to hepatotoxicity, renal toxicity, and genetic damage. Moreover, limonin also has complex impacts on hepatic metabolic enzyme. Pharmacokinetic studies have demonstrated that limonin has poor bioavailability, and the reduction, hydrolysis, and methylation are the main metabolic pathways of limonin. We also found that the position and group of the substituents of limonin are key in affecting pharmacological activity and bioavailability. However, some issues still exist, such as the mechanism of antioxidant activity of limonin not being clear. In addition, there are few studies on the toxicity mechanism of limonin, and the effects of limonin concentration on pharmacological effects and toxicity are not clear, and no researchers have reported any ways in which to reduce the toxicity of limonin. Therefore, future research directions include the mechanism of antioxidant activity of limonin, how the concentration of limonin affects pharmacological effects and toxicity, finding ways to reduce the toxicity of limonin, and structural modification of limonin—one of the key methods necessary to enhance pharmacological activity and bioavailability.